2021
DOI: 10.1002/cctc.202101072
|View full text |Cite
|
Sign up to set email alerts
|

Helical Bisphosphinites in Asymmetric Tsuji‐Trost Allylation: a Remarkable P:Pd Ratio Effect

Abstract: This article discloses a study on a chiral bis-phosphorylatedhelical ligand in the palladium-catalyzed Tsuji-Trost allylation. The use of 2,15-bisphosphinite-[6]-helicenes revealed a remarkable ligand effect, in which the (R) and (S) isomeric products can be selectively formed as a direct function of the amount of ligand introduced. Investigation of the organometallic species involved through 31 P NMR spectroscopic analysis of a model complex and X-Ray diffraction analysis together with DFT calculations shed l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Helicenes are chiral; as a result, they are expected to have specific functionalities. Recently, helicenes have been widely applied in various fields [ 1 , 2 , 3 , 4 , 5 ], such as organic semiconductors [ 6 , 7 , 8 , 9 , 10 ], asymmetric catalysis [ 11 , 12 , 13 , 14 , 15 , 16 ], and molecular recognition [ 17 , 18 , 19 , 20 , 21 , 22 ], due to their diverse functionalities in materials. Many studies have also been reported on self-assembly phenomena at metal surfaces [ 23 , 24 , 25 , 26 ] caused by interactions with the π-orbitals of helicenes.…”
Section: Introductionmentioning
confidence: 99%
“…Helicenes are chiral; as a result, they are expected to have specific functionalities. Recently, helicenes have been widely applied in various fields [ 1 , 2 , 3 , 4 , 5 ], such as organic semiconductors [ 6 , 7 , 8 , 9 , 10 ], asymmetric catalysis [ 11 , 12 , 13 , 14 , 15 , 16 ], and molecular recognition [ 17 , 18 , 19 , 20 , 21 , 22 ], due to their diverse functionalities in materials. Many studies have also been reported on self-assembly phenomena at metal surfaces [ 23 , 24 , 25 , 26 ] caused by interactions with the π-orbitals of helicenes.…”
Section: Introductionmentioning
confidence: 99%